STUDI PENURUNAN Fe2+ DENGAN UNIT SARINGAN PASIR CEPAT MEDIA PASIR LAUT - Oktiawan, Wiharyanto; Krisbiantoro, Krisbiantoro (Universitas Diponegoro, 2007)
Abstract Iron is mineral that cause staining of plumbing fixtures and laundered clothes as wall as produce distinct taste and odors in a drinking water. Aeration is alternative processes for the removal of iron. Sedimentation and filtration will remove the iron precipitates formed in the aeration device. This research uses 2 stages in testing; they are the batch filter and the column filter. On each of the stages we try using activated sand media. This media is known to able to decrease the Fe2+.The water spring is from the 2nd deep well at the Prambanan water treatment facility. The goal from this research is to find the criteria design on surface loading and to find out the effectiveness in reducing Fe2+ that is in the water by using the media of activated sand. From this experiment we found that the maximal filtration speed on activated sand is 11,05 m/hour. Calculation analysis shows that the coefficient. Figure of Fe2+ in the batch filter on Ngrenehan beach ocean sand filter is λ1=0,40± 0, l0 m -1 with the average on reducing Fe2+ 21,37%. This figure is small if it is compare to the coefficient figure of Fe2+ in the batch activated sand filter is λ1=0,92± 0, l6 m -1 with the average on reducing Fe2+ 42,27%. Keywords : Ngrenehan beach ocean sand filte, rapid sand filter. Activated sand, filtration speed. removal coefficient